Psychological Communication in the Self Concept and Cultural Identity of the People of Indramayu Regency through Ngarot Tradition - Yeni Nuraeni; Ashur Harmadi; Sugiharti Binastuti; Diana Sari (Jurnal Komunikasi Ikatan Sarjana Komunikasi Indonesia, 2024)
This research aims to find out psychological communication through the self-concept and cultural identity of the people of  Indramayu Regency using a symbolic interaction theory (mind, self and society). Ngarot tradition evolved within Lelea community in Indramayu Regency, West Java, where they celebrated  the tradition every year. The word Ngarot comes from Sanskrit which means to cleanse oneself from stains and sins from the wrong behavior of a person or a group of people in the past.  Ngarot tradition is closely related to the cultural identity that is shaped in the society and serves as the symbols of the next generation. This research uses a descriptive qualitative method. The results of the research show that the self-concept of the people of  Indramayu Regency is designed to appreciate and respect the culture, by preserving it through agricultural activities, as well as to express  gratitude to God. The cultural identity of the Lelea community can be seen from various things that developed in the area, including those in the socio-cultural, economic, and religious fields.